Deficiency of TRPM2 leads to embryonic neurogenesis defects in hyperthermia - Li, Yanxin (Sci Adv, 2020)
Temperature homeostasis is critical for fetal development. The heat sensor protein TRPM2 (transient receptor potential channel M2) plays crucial roles in the heat response, but its function and specific mechanism in brain development remain largely unclear. Here, we observe that TRPM2 is expressed in neural stem cells. In hyperthermia, TRPM2 knockdown and knockout reduce the proliferation of neural progenitor cells (NPCs) and, accordingly, increase premature cortical neuron differentiation. In terms of the mechanism, TRPM2 regulates neural progenitor self-renewal by targeting SP5 (specificity protein 5) via inhibiting the phosphorylation of β-catenin and increasing β-catenin expression. Furthermore, the constitutive expression of TRPM2 or SP5 partly rescues defective NPC proliferation in the TRPM2-deficient embryonic brain. Together, the data suggest that TRPM2 has a critical function in maintaining the NPC pool during heat stress, and the findings provide a framework for understanding how the disruption of the TRPM2 gene may contribute to neurological disorders.